The Role of Cooperatives in Shallots Production in Sukasari Kidul Village Majalengka Regency - Ainurrahma, Annisa; Suryantini, Any; Mulyo, Jangkung Handoyo (HABITAT, 2025)
Majalengka regency as a shallots center contributes 22.7% of shallot production in West Java. This agribusiness opportunity can be pursued through downstreaming, but there are constraints in economic institutions. Today, agricultural cooperatives have a diminishing role and have been replaced by other stakeholders who partner with farmers. This problem does not prevent some farmers in Sukasari Kidul Village from forming a cooperative that is expected to help farmers to increase production. This study aims to determine the role of Mandiri Jaya Cooperative on shallot production in Sukasari Kidul Village, Argapura District, Majalengka Regency. The sampling method is non-probability sampling with purposive sampling respondent selection criteria. The number of respondents used was 60 farmers. The data analysis method used was descriptive quantitative, namely multiple linear regression analysis of the Cobb-Douglas production function. The results show that farmer members perceive agricultural cooperative services as high, meaning that the performance of Mandiri Jaya Cooperative supports shallot production. Other factors that influence increasing shallot production are land area, urea fertilizer, pesticides, labor, education level.